2019
DOI: 10.1021/acsami.8b21363
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Osseointegration Ability of Poly(lactic acid) via Tantalum Sputtering-Based Plasma Immersion Ion Implantation

Abstract: Poly(lactic acid) (PLA) is the most utilized biodegradable polymer in orthopedic implant applications because of its ability to replace regenerated bone tissue via continuous degradation over time. However, the poor osteoblast affinity for PLA results in a high risk of early implant failure, and this issue remains one of the most difficult challenges with this technology. In this study, we demonstrate the use of a new technique in which plasma immersion ion implantation (PIII) is combined with a conventional D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 51 publications
1
30
0
1
Order By: Relevance
“…Hence, plasma-immersion ion implantation (PIII) is an effective approach in ion bombardment of inhomogeneous surfaces. 313 Park et al 321 investigated the effects of tantalum ion immersion on the poly(lactic acid) (PLA) surface for improving its osteoblast affinity by using PIII in combination with conventional direct current magnetron sputtering. They revealed that tantalum ion-doped surfaces have twice the surface roughness and improve adhesion stability in comparison with tantalum-coated PLA surfaces.…”
Section: Impact Of Biomaterials Surface Chemical Properties On Biologimentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, plasma-immersion ion implantation (PIII) is an effective approach in ion bombardment of inhomogeneous surfaces. 313 Park et al 321 investigated the effects of tantalum ion immersion on the poly(lactic acid) (PLA) surface for improving its osteoblast affinity by using PIII in combination with conventional direct current magnetron sputtering. They revealed that tantalum ion-doped surfaces have twice the surface roughness and improve adhesion stability in comparison with tantalum-coated PLA surfaces.…”
Section: Impact Of Biomaterials Surface Chemical Properties On Biologimentioning
confidence: 99%
“…Tantalum doped ions improve the osseointegration and osteogenesis of implanted PLA surfaces in vivo through improving surface hydrophilic properties. 321 Researchers also studied macrophage polarization responses to titanium implants doped with magnesium (0.1-0.35%). 322 Doping magnesium ions on the surface causes a greater expression of type 2 macrophages, anti-inflammatory cytokines (such as IL-4 and IL-10) as well as genes encoding bone morphogenetic protein 2 (BMP2) and VEGF.…”
Section: Impact Of Biomaterials Surface Chemical Properties On Biologimentioning
confidence: 99%
“…Moreover, porous Ta remarkably stimulated the proliferation and mineralization of osteoblasts as compared with cobalt chromium and Ti based biomaterials [ 7 ]. Furthermore, Ta allows bone tissues on on/in-growth and stimulates osteogenesis to achieve osseointegration, promoting the initial and long-term stability of implants [ 8 ]. It has been suggested that a natural thin layer of tantalum pentoxide existing on Ta surface might play a key role on its excellent biocompatibility, corrosion resistance, bioactivity as well as positive cell/tissue responses for bone on/in-growth [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Miyaza et al reported that the deposition of bone-like mineralization on the Ta surface was due to the presence of the Ta-OH structure [ 73 ]. Appropriate hydrophilicity and water contact angle were also regarded as crucial factors for the bioactivities of Ta [ 74 ]. It was also reported that the osteogenic property of Ta may result from its distinct elastic modulus [ 75 , 76 ], because appropriate elastic modulus could conduct the osteogenic differentiation by triggering the integrins [ 77 ].…”
Section: Summary and Personal Perspectivementioning
confidence: 99%